Application of plasma‐activated water as an antimicrobial washing agent of fresh leafy produce. Issue 12 (25th August 2021) - Dimitrakellis, Panagiotis; Giannoglou, Marianna; Xanthou, Zacharoula Maria; Gogolides, Evangelos; Taoukis, Petros; Katsaros, George
Abstract: Plasma‐activated water (PAW) was investigated as a "green" antimicrobial washing agent for decontamination of ready‐to‐eat rocket salads. PAW was generated using a dielectric barrier discharge jet and the plasma chemistry was correlated to the PAW characteristics. The low helium flow rates favored the NO x formation and resulted also in higher reactive species concentration upon storage. PAW activity was retained even after 12 days of storage at low temperatures. The application of fresh and 7‐days‐stored PAW as washing agents resulted in significant microbial load reduction, whereas the quality indices of PAW‐treated rocket leaves were retained. Finally, the PAW treatment increased the shelf‐life of the leafy salad by a factor of 2.5 upon storage at 5°C, demonstrating the potential application of plasma technology in the processing and shelf‐life extension of sensitive food products. Abstract : Plasma‐activated water (PAW) was investigated as a "green" antimicrobial washing agent for decontamination of ready‐to‐eat rocket salads. The PAW generated using a plasma jet in contact with deionized water was active even after 12 days of storage at low temperatures. The washing of rocket leaves with PAW resulted in significant microbial load reduction without affecting the quality attributes, leading to an almost 2.5‐times increase in shelf‐life